A Fuzzy Logic Positional-Based Controller For Sensorbased Robotic Motion Planning - Khaksar W.; Yousefi M.; Saharia K.S.M.; Ismail F.B. (Asian Research Publishing Network, 2023)
Motion planning is a critical task for any robotic system. Despite the large volume of research in this field, the computational complexity of the motion planning and the increasing potential application domains require more accurate and efficient motion planning algorithms. In this paper, a novel positional-based motion controller is proposed which requires very little amount of information from the robots sensory system. The proposed controller evaluates candidate positions of the robot and selects the most promising ones according to the output of a fuzzy logic controller. The designed controller defines three positional variables for destination evaluation in order to improve the path length and runtime of the solutions. The performance of the proposed planner is tested through computer simulation in different types of environments. Simulation studies indicate the efficiency and robustness of the proposed algorithm. 2006-2015 Asian Research Publishing Network (ARPN). All rights reserved.